2004
DOI: 10.1134/1.1787120
|View full text |Cite
|
Sign up to set email alerts
|

Modeling improvement of spectral response of solar cells by deployment of spectral converters containing semiconductor nanocrystals

Abstract: -A planar converter containing quantum dots as wavelength-shifting moieties on top of a solar cell was studied. The highly efficient quantum dots are to shift the wavelengths where the spectral response of the solar cell is low to wavelengths where the spectral response is high in order to improve the conversion efficiency of the solar cell. It was calculated that quantum dots with an emission at 603 nm increase the multicrystalline solar cell short-circuit current by nearly 10%. Simulation results for planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Spectral downconverters convert the wavelengths where the spectral response is low to wavelengths where the spectral response is high. [2][3][4][5] A promising method can help single-crystalline Si (sc-Si) solar cells capture more energy from the solar spectrum via spectral DC of lanthanide rare earth (RE) ions near-infrared (NIR) quantum cutting (QC): Cutting an ultraviolet (or a blue photon) into two or more NIR photons, which can be well absorbed by sc-Si solar cells, will reduce the energy loss related to thermalization of hot charge carriers and then improve the ECE of sc-Si solar cells. 6 The potential applications of NIR QC in sc-Si solar cells have attracted a lot of recent research attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral downconverters convert the wavelengths where the spectral response is low to wavelengths where the spectral response is high. [2][3][4][5] A promising method can help single-crystalline Si (sc-Si) solar cells capture more energy from the solar spectrum via spectral DC of lanthanide rare earth (RE) ions near-infrared (NIR) quantum cutting (QC): Cutting an ultraviolet (or a blue photon) into two or more NIR photons, which can be well absorbed by sc-Si solar cells, will reduce the energy loss related to thermalization of hot charge carriers and then improve the ECE of sc-Si solar cells. 6 The potential applications of NIR QC in sc-Si solar cells have attracted a lot of recent research attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the PL conversion, a He-Cd laser beam (λ = 325 nm) shone through, and a bright red line could be clearly seen by the naked eye. The increase in I SC again demonstrated the validity of PL conversion in increasing the I SC of crystalline Si solar cells [8,11] . However, the open-circuit voltage, U OC , was nearly constant with the change in C Si .…”
mentioning
confidence: 60%
“…In 2004 van Sark et al [9] studied CdSe quantum dots (QDs) as spectral shifting components for photovoltaic applications and have shown that QDs can be used as an alternative material for down-shifting converters on top of multi-crystalline and amorphous silicon solar cells. Later, Hogson et al [10] reported the application of CdSe/ZnS QD/PMMA luminescent down-shifting films to CdTe solar cells.…”
Section: Introductionmentioning
confidence: 99%